Management buy-outs phenomenon in Malaysia: its performance / Mohamad Asmady Shahadan - Shahadan, Mohamad Asmady (1994)
This project paper is mainly focusing on the performance of the management buy-outs companies. It is believed that the buy-out exercise would not only be a great opportunity to create wealth but eventually manage to turn an ailing company to a brighter company. Thus in order to examine the performance of buyouts companies, few series of analysis such as gap analysis, growth analysis, price movement analysis, returns analysis and multiple regression analysis for the selected variables have been conducted. It was noted that the turnover, total costs and gross domestic product are significant to the profitability of the buy-out companies.